2009
DOI: 10.1007/s10811-009-9458-1
|View full text |Cite
|
Sign up to set email alerts
|

Is photosynthesis a requirement for paralytic shellfish toxin production in the dinoflagellate Alexandrium minutum algal–bacterial consortium?

Abstract: While there is increasing evidence that marine bacteria are involved in the production of paralytic shellfish toxins in algal blooms, the exact roles of the bacteria and microalgae have proved elusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…This cellular amount of PST started to decline after 6 days of darkness ( Figure 8 ). Similar results were reported in Alexandrium minutum , that STX content disappeared completely after incubating the culture in the dark for 22 days [ 35 ]. This change of toxicity after continuous darkness further indicated that light energy is crucial for toxin biosynthesis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This cellular amount of PST started to decline after 6 days of darkness ( Figure 8 ). Similar results were reported in Alexandrium minutum , that STX content disappeared completely after incubating the culture in the dark for 22 days [ 35 ]. This change of toxicity after continuous darkness further indicated that light energy is crucial for toxin biosynthesis.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, from our study, growth of the cell density of AC-T stopped on day 7 ( Figure 2 ) and the toxin content per cell increased by nearly 3.5 folds on day 20 with 10% of normal phosphate provision ( Figure 4 A). The most common explanation of this phenomenon was the accumulation of toxins produced inside undivided algal cells when there was insufficient phosphate for DNA synthesis [ 35 ] prerequisite to cell division. This was supported by the observation that cell volumes of AC-T cells increased under phosphate limitation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the yield of saxitoxin per cell in the dinoflagellate Alexandrium catenella is proportional to hours of daylight (Proctor et al 1975). Also, A. minutum is not capable of producing saxitoxin after a 22 d incubation period in the dark, while parallel light-grown cultures produced 1.17 µg per 10 000 algal cells (Maas & Brooks 2010). pCO 2 and/or pH changes affect toxicity of the diatom genus Pseudo-nitzschia, which causes notoriously damaging blooms along the Pacific coast of North America and elsewhere around the world (Scholin et al 2000, Trainer et al 2000, 2009, Schnetzer et al 2007.…”
Section: Effects Of Individual Global Change Factors On Harmful Algaementioning
confidence: 99%
“…Some studies have analyzed toxin production and toxin profile diversity in axenic batch cultures of A. tamarense (= A. pacificum ) (Omura, 1999), while the results of other studies have demonstrated that the low growth rate of axenic A. tamarense is due to nutrient deficiencies rather than a lack of bacteria (Singh et al 1982; Dantzer and Levin, 1997). It has been suggested that the effects of bacteria on PSP toxin production by marine Alexandrium species can be explained by altered toxin synthesis pathways, by algae or bacteria alone, or by algal-bacterium interactions (Maas and Brooks 2010). Although the axenic culturing of dinoflagellates poses multiple difficulties, bacteria-free cultures are useful for understanding the characteristics of PSP toxins and the underlying physiology that affects their production by the dinoflagellate, with no complications caused by bacterial interactions.…”
Section: Introductionmentioning
confidence: 99%